2006
DOI: 10.1093/hmg/ddl036
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin pre-treatment protects against apoptosis

Abstract: Macroautophagy (generally referred to as autophagy) mediates the bulk degradation of cytoplasmic contents, including proteins and organelles, in lysosomes. Rapamycin, a lipophilic, macrolide antibiotic, induces autophagy by inactivating the protein mammalian target of rapamycin (mTOR). We previously showed that rapamycin protects against mutant huntingtin-induced neurodegeneration in cell, fly and mouse models of Huntington's disease [Ravikumar, B., Duden, R. and Rubinsztein, D.C. (2002) Aggregate-prone protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
266
2
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 378 publications
(294 citation statements)
references
References 35 publications
23
266
2
3
Order By: Relevance
“…We also measured the amount of apoptosis in HeLa cells when autophagy was inhibited by 3-methyladenine (Supplementary Figure S5). Although 3-methyladenine was toxic and its toxicity synergized with that of STS, as shown earlier in other cell systems (Ravikumar et al, 2006), nevertheless, the same amount of protection by Bcl-2 variants was found in cells expressing Bcl-2 alone, or Bcl-2 and Beclin-1 (measured by PARP cleavage). These results strengthen the conclusion that Beclin-1 does not prevent Bcl-2 from inhibiting apoptosis irrespective of whether autophagy is active or inactive.…”
Section: Resultssupporting
confidence: 72%
“…We also measured the amount of apoptosis in HeLa cells when autophagy was inhibited by 3-methyladenine (Supplementary Figure S5). Although 3-methyladenine was toxic and its toxicity synergized with that of STS, as shown earlier in other cell systems (Ravikumar et al, 2006), nevertheless, the same amount of protection by Bcl-2 variants was found in cells expressing Bcl-2 alone, or Bcl-2 and Beclin-1 (measured by PARP cleavage). These results strengthen the conclusion that Beclin-1 does not prevent Bcl-2 from inhibiting apoptosis irrespective of whether autophagy is active or inactive.…”
Section: Resultssupporting
confidence: 72%
“…It has been shown that autophagy can either collaborate with apoptosis either to promote cell death or to prevent apoptotic cell death [38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Given the potential role of both autophagy and BNIP3 in the regulation of cell death and cell survival, we investigated their putative role in etoposide-induced cell death and the protection provided by hypoxia. 40,000 cells were seeded on glass coverslips in 24-well culture plates. At the end of the incubation in serum-free CO 2 -independent medium (Invitrogen, Carlsbad, USA) supplemented with 1 mM L-glutamine (Sigma, St Louis, USA) with or without etoposide (Sigma, St Louis, USA) at 50 μM, under hypoxia or under normoxia, medium was removed and cells were fixed for 10 min with PBS containing 4% paraformaldehyde and then washed 3 x 5 min in PBS.…”
Section: Introductionmentioning
confidence: 99%
“…For example, increased autophagy in nutrient deprived or growth factorwithdrawn cells allows cell survival (16,17) by inhibiting apoptosis. Autophagy also protects cells from various other apoptotic stimuli (18). It is not clear how autophagy stops cells from undergoing apoptosis; one suggested mechanism is the sequestration of damaged mitochondria (18) thus preventing released cytochrome c from being able to form a functional apoptosome in the cytoplasm.…”
mentioning
confidence: 99%
“…Autophagy also protects cells from various other apoptotic stimuli (18). It is not clear how autophagy stops cells from undergoing apoptosis; one suggested mechanism is the sequestration of damaged mitochondria (18) thus preventing released cytochrome c from being able to form a functional apoptosome in the cytoplasm. Recent work suggests that autophagy can also protect cells from caspaseindependent death that occurs after Mitochondrial Outer Membrane Permeabilization (MOMP) in the presence of caspase inhibitors.…”
mentioning
confidence: 99%